The Implementation of the Role Playing Method to Improve Students’ Conceptual Understanding of Solid Figures in Grade V at SD Negeri 04 Talang Kelapa, Banyuasin, Palembang - Azizah Purwitasari; Samuel Slamet Santosa (Journal of Educational Learning and Innovation (ELIa), 2025)
This study was motivated by problems identified in the mathematics learning process, namely the lack of innovation, motivation, and opportunities for students to actively participate. The purpose of this research was to determine the effect of the Role Playing learning model on the mathematical conceptual understanding of fifth-grade students at SD Negeri 4 Talang Kelapa. The research problem was formulated as follows: “Is the Role Playing method effective in increasing student engagement in learning mathematics on the topic of plane geometry?” This study employed a quantitative approach with a quasi-experimental design. The research subjects consisted of 28 fifth-grade students divided into 7 groups, each comprising 4 students, selected using purposive sampling. The assessment instruments included observations of group collaboration, active participation, and conceptual understanding, measured through performance observation and group quiz question-and-answer sessions. Data analysis involved the normality test, homogeneity test, and paired sample t-test for hypothesis testing. The results revealed a significant improvement in students’ mathematical conceptual understanding. The average activeness score increased from 28.64 (pretest) to 43.14 (posttest), motivation rose from 24.21 to 36.00, and conceptual understanding of solid figures increased from 61.25 to 79.80. It can be concluded that the Role Playing method has a significant positive impact on students’ activeness, motivation, and conceptual understanding in mathematics learning, particularly in the topic of solid figures.